Effect of strain paths on the evolution of texture and work hardening in AA 5052 sheets during continuous confined strip shearing deformation - Chung, YH; Ahn, JP; Kim, HD; Hwang, BB; Engler, O; Huh, MY (TRANS TECH PUBLICATIONS LTD, 2002)
In order to investigate the effect of strain path changes on the development of a shear texture and the work hardening during continuous confined strip shearing (CCSS) based on the equal channel angular pressing (ECAP), the procedure of sample feeding was varied (unidirectional vs. reversible). The evolution of texture and microstructure during CCSS with difference strain paths was studied by texture measurements and microstructure observations. Results of FEM simulations indicated that the deformation during CCSS is not homogeneous throughout the strip thickness, in particular near the upper surface. The work hardening of the deformed material was virtually not affected by the sample feeding method, whereas the evolution of texture during CCSS strongly depended on the imposed strain path.
Keywords: MICROSTRUCTURE